Establishment and Evaluation of a Rat Model of Non-Puerperal Mastitis - YIN Yulian; MA Lina; TU Siyuan; CHEN Ling; YE Meina; CHEN Hongfeng (Shiyan dongwu yu bijiao yixue, 2024)
Objective This study aims to establish a non-puerperal mastitis (NPM) rat model by simulating hyperprolactinemia and immune-inflammatory states, and to evaluate its local inflammatory characteristics in the mammary gland, thereby laying the foundation for research on the diagnosis and treatment of this clinically challenging disease. Methods Twelve SPF-grade Wistar female rats were evenly divided into a control group and a model group. During the experiment, the control group received no experimental treatment or medication. The model group received daily subcutaneous injections of 100 mg/kg metoclopramide hydrochloride for 7 consecutive days. Serum prolactin (PRL) levels were measured using ELISA on the 10th, 20th, and 30th days after the first injection. After 7 days of injections, 200 μL of lactating SD rat milk was mixed with 200 μL of complete Freund's adjuvant to prepare an oil-in-water emulsion, which was administered by multiple subcutaneous injections into the back of the Wistar rats for the initial immunization. Seven days after the initial immunization, the emulsion was injected subcutaneously into the third, fourth, and fifth mammary glands for the final immunization. After the final immunization, the rats were observed for 28 days for changes in mammary gland appearance, and the size of mammary nodules was calculated. On the 3rd, 7th, 14th, and 28th days, hematoxylin-eosin (HE) staining was used to analyze mammary tissue morphology. Immunohistochemistry was employed to detect CD138 expression levels. ELISA was used to measure the levels of interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, and inducible nitric oxide synthase (iNOS) in mammary tissue to comprehensively assess the model. Results Rats in the model group exhibited mammary skin ulceration and foul odor at the ulcer sites. Palpation and ultrasound revealed the formation of mammary nodules. HE staining showed that on the 3rd day after the final immunization, normal ductal and lobular structures in the mammary glands disappeared, with significant infiltration of plasma cells. On the 7th day, ductal dilation, epithelial necrosis and detachment, and pronounced periductal plasma cell and lymphocyte (predominantly T-lymphocytes) infiltration were observed. On the 14th day, there was a proliferation of fibrofatty tissue, small blood vessels, and granulation tissue, with scattered plasma cells in the interstitium. By the 28th day, inflammatory cell infiltration and fibrous tissue proliferation were reduced, with granuloma formation. Serum PRL levels in the model group were significantly increased on the 10th day (P<0.05) and the 20th day (P<0.001). IL-6 and TNF-α levels in mammary tissue were higher in the model group compared to the control group on the 3rd, 7th, 14th, and 28th days (P<0.05). IL-1β levels were higher on the 3rd, 7th, and 14th days compared with the control group (P<0.01) but lower than the control group on the 28th day (P>0.05). iNOS levels were significantly higher on the 7th day after the final immunization (P<0.001). Conclusion A successful NPM model was established in rats, which exhibited typical pathological features such as local mammary masses, abscesses, ulcers, ductal dilation and plasma cell infiltration. This model can serve as a foundation for further research into the diagnosis and treatment of this clinically challenging disease.